2023
DOI: 10.1021/acsnano.3c02102
|View full text |Cite
|
Sign up to set email alerts
|

Typhaneoside-Tetrahedral Framework Nucleic Acids System: Mitochondrial Recovery and Antioxidation for Acute Kidney Injury treatment

Abstract: Acute kidney injury (AKI) is not only a worldwide problem with a cruel hospital mortality rate but also an independent risk factor for chronic kidney disease and a promoting factor for its progression. Despite supportive therapeutic measures, there is no effective treatment for AKI. This study employs tetrahedral framework nucleic acid (tFNA) as a vehicle and combines typhaneoside (Typ) to develop the tFNA-Typ complex (TTC) for treating AKI. With the precise targeting ability on mitochondria and renal tubule, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 64 publications
(21 citation statements)
references
References 75 publications
1
20
0
Order By: Relevance
“…Due to the source of its components, tFNAs are highly programmable and easy to modify and label with very low immunogenicity. Recently, studies have found that tFNAs can penetrate different cells to affect their various biological activities. Moreover, our previous research has found that tFNAs or its derivatives could inhibit inflammation via regulating the IL-17 pathway. , Li and his colleagues discovered that tFNAs loaded with resveratrol could suppress inflammation and ameliorate insulin resistance via inhibiting Th1 and Th17 cell activation to reduce the production of IL-17 . In our study, tFNAs were used as a treatment option for AS, and significant therapeutic effects were observed both in vivo and in vitro .…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…Due to the source of its components, tFNAs are highly programmable and easy to modify and label with very low immunogenicity. Recently, studies have found that tFNAs can penetrate different cells to affect their various biological activities. Moreover, our previous research has found that tFNAs or its derivatives could inhibit inflammation via regulating the IL-17 pathway. , Li and his colleagues discovered that tFNAs loaded with resveratrol could suppress inflammation and ameliorate insulin resistance via inhibiting Th1 and Th17 cell activation to reduce the production of IL-17 . In our study, tFNAs were used as a treatment option for AS, and significant therapeutic effects were observed both in vivo and in vitro .…”
mentioning
confidence: 62%
“…Tetrahedral frame nucleic acids (tFNAs) are bioactive nanomaterial with tetrahedron-like structures that have been widely studied in the biomedical field. Its editability allows it to carry coding sequence in a framework structure for the treatment of specific diseases. The small size and the negative surface potential of tFNAs determine that it could be quickly ingested by cells to exert various biological effects.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, nucleic acid aptamer-guided drug conjugates (ApDCs) have attracted interest for their extensive targeting features and cost-effectiveness. The nucleic acid aptamers are DNA or RNA with unique sequences and conformations to specifically bind with target molecules, such as small molecules, peptides, and protein. , Aptamers can be easily designed, reproducibly manufactured, and diversely modified for various biological applications. , However, the reported ApDCs were limited with short half-time (within ∼1 h) and low drug-carrier ability (the drug/carrier ratio is limited to 1:1). , Therefore, carrying a sufficient drug dose of ApDCs remains a key question to be addressed. In our previous work, we have demonstrated that the DNA or RNA aptamers could be modified onto tetrahedral framework nucleic acid (tFNA). , The tFNA consists of four single-stranded DNAs (ssDNAs), and the anti-HER2 aptamer (HApt) can be modified onto the end of ssDNA to form the HApt-embedded DNA tetrahedron (HApt-tFNA) . Previous studies have demonstrated the excellent affinity of HApt-tFNA to HER2-positive breast cancer cells. , Therefore, if the cytotoxic drugs were conjugated onto the ssDNAs of HApt-tFNA, new ApDCs would be created with multiplied cargos that could largely enhance antitumor effects.…”
Section: Introductionmentioning
confidence: 99%
“…DNA polyhedron was proposed by Turberfield and colleagues . Tetrahedral framework nucleic acids (tFNAs) are supposed to make up a stable polyhedron; they are self-assembled by four single DNA strands. In contrast to the cytotoxicity and low clearance deficiency of traditional nanomaterials, natural nucleic acid nanomaterial tFNAs attracted much attention for their biocompatibility and biodegradability. Compared to the simply structured double-strand DNA, tFNAs demonstrate better cell penetration ability, a more stable structure, and abundant drug loading sites. , They can also modulate the biological behaviors of cells, and be modified by size and dimensions at will to be used as a wide range of carriers. , …”
Section: Introductionmentioning
confidence: 99%